Human & inhuman opposition to the buffaloes of the Guaporé valley – In Rondônia - Gonçalves, Marcus Fabiano; Oliveira, Terezinha Azevedo; Santos, Anna Luíza Soares Diniz; Viana, Thiago da Silva (Seven Editora, 2023)
Human & inhuman opposition to the buffaloes of the Guaporé valley – In RondôniaFrom research that has the power to analyze the possibilities of the existence or not of human and legal impediments, relating to the buffaloes of the Guaporé Valley, in Rondônia, and whether there is a link between buffaloes and regional environmental preservation. And in this section, we investigated the correlation between buffalo breeding in this territory and the environmental maintenance of the region. The methodology was applied with bibliographic reference surveys, and questionnaires and graphic demonstration of results aimed at clarifying the theses that were raised. And this work was justified by its thematic relevance, which allows a reflection on the benefit of preserving buffaloes in coexistence with humans. This is a consideration and analysis of the damage caused by man in the misuse of nature, with the devastation of forests, aquifers, and their incident and serious consequences, with the consequent energy crisis, dust clouds, and the desertification of large areas. , and its rivers - resulting from this environmental imbalance: unemployment, increased poverty and hunger. DOI:https://doi.org/10.56238/interdiinovationscrese-087